Nitrite as a Stimulus for Ammonia-Starved Nitrosomonas europaea - Laanbroek, Hendrikus J. (American Society for Microbiology, 2002)
Ammonia-starved cells of Nitrosomonas europaea are able to preserve a high level of ammonia-oxidizing activity in the absence of ammonium. However, when the nitrite-oxidizing cells that form part of the natural nitrifying community do not keep pace with the ammonia-oxidizing cells, nitrite accumulates and may subsequently inhibit ammonia oxidation. The maintenance of a high ammonia-oxidizing capacity during starvation is then nullified. In this study we demonstrated that cells of N. europaea starved for ammonia were not sensitive to nitrite, either when they were starved in the presence of nitrite or when nitrite was supplied simultaneously with fresh ammonium. In the latter case, the initial ammonia-oxidizing activity of starved cells was stimulated at least fivefold.